Distribution and bioconcentration of heavy metals in a tropical aquatic food web: A case study of a tropical estuarine lagoon in SE Mexico. (March 2016) - Mendoza-Carranza, Manuel; Sepúlveda-Lozada, Alejandra; Dias-Ferreira, Celia; Geissen, Violette
Abstract: Despite the increasing impact of heavy metal pollution in southern Mexico due to urban growth and agricultural and petroleum activities, few studies have focused on the behavior and relationships of these pollutants in the biotic and abiotic components of aquatic environments. Here, we studied the bioaccumulation of heavy metals (Cd, Cr, Ni, Pb, V, Zn) in suspended load, sediment, primary producers, mollusks, crustaceans, and fish, in a deltaic lagoon habitat in the Tabasco coast, with the aim to assess the potential ecological risk in that important wetland. Zn showed the highest concentrations, e.g., in suspended load (mean of 159.58 mg kg −1 ) and aquatic consumers (15.43–171.71 mg kg −1 ), particularly Brachyura larvae and ichthyoplankton (112.22–171.71 mg kg −1 ), followed by omnivore Callinectes sp. crabs (113.81–128.07 mg kg −1 ). The highest bioconcentration factors (BCF) of Zn were observed for planktivore and omnivore crustaceans (3.06–3.08). Zn showed a pattern of distribution in the food web through two pathways: the pelagic (where the higher concentrations were found), and the benthic (marsh plants, sediment, mollusk, fish). The other heavy metals had lower occurrences in the food web. Nevertheless, high concentrations of Ni and Cr were found in phytoplankton and sediment (37.62–119.97 mg kg −1 ), and V in epiphytes (68.64 mg kg −1 ). Ni, Cr, and Cd concentrations in sediments surpassed international and national threshold values, and Cd entailed a "considerable" potential risk. These heavy metals are most likely transferred into the food web up to fishes through the benthic pathway. Most of the collected fishes are residents in this type of habitat and have commercial importance. Our results show that the total potential ecological risk in the area can be considered as "moderate". Nevertheless, heavy metal values were similar or surpassed the values from other highly industrialized tropical coastal regions. Highlights: Coastal environment of southern Mexico had high levels of heavy metal. Zn was the most frequent and abundant heavy metal in the environment and biota. Cr, Pb and Cd concentrations in commercial species exceeded threshold values. The sedimentary trophic web was the principal via to heavy metal distribution. The potential ecological risk in San Pedrito Lagoon was classified as moderate. Abstract : We studied the behavior of heavy metal pollution (Cd, Cr, Ni, Pb, V, Zn) in a tropical aquatic biotic and abiotic components; our results indicate that main pollutant via is the sedimentary trophic web; ecological risk for Cd was "considerable", whereas for others 5 metals was classified as "low".